2004
DOI: 10.1001/archneur.61.5.673
|View full text |Cite
|
Sign up to set email alerts
|

The AED (Antiepileptic Drug) Pregnancy Registry

Abstract: A hospital-based pregnancy registry can establish the fetal risk of major malformations for a commonly used drug. Prenatal exposure to phenobarbital is associated with a significantly increased risk of fetal abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(121 citation statements)
references
References 24 publications
(14 reference statements)
5
112
1
2
Order By: Relevance
“…There is not any particular rationale or specific reason that PB has been listed as a scheduled substance other than that it is a barbiturate and therefore has a potential to be a drug of abuse. 3 In China, where large demonstration project and national epilepsy programs have taken place, there have been no major negative impact on cognitive function of people with convulsive seizures treated with PB, but instead cognitive gains have been observed as a result of PB treatment. 4 Treatment guidelines call for controlled substances such as AEDs to be readily available, but this has not been the case in many LMICs.…”
Section: Essential Drug Status Versus Controlled Substance Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…There is not any particular rationale or specific reason that PB has been listed as a scheduled substance other than that it is a barbiturate and therefore has a potential to be a drug of abuse. 3 In China, where large demonstration project and national epilepsy programs have taken place, there have been no major negative impact on cognitive function of people with convulsive seizures treated with PB, but instead cognitive gains have been observed as a result of PB treatment. 4 Treatment guidelines call for controlled substances such as AEDs to be readily available, but this has not been the case in many LMICs.…”
Section: Essential Drug Status Versus Controlled Substance Statusmentioning
confidence: 99%
“…16 The teratogenic risk of PB in pregnancy may be higher than that of some other AEDs. 3 But for the moment, LMICs are often presented with either having a treatment with PB or having no treatment at all. 17 Therefore, any barriers to its use in countries needing it should be reduced.…”
Section: Potential Cons Of Pbmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Phenobarbital is associated with a significantly increased risk of fetal abnormalities. 21 Hepatic metabolism is induced by PB, and the clearance of concomitantly administered hepatically metabolized drugs, including hormonal contraceptives, 15 is increased.…”
Section: Phenobarbitalmentioning
confidence: 99%
“…Major malformations affected 4.5% and 8.6% of these infants, respectively. Other authors observed major birth defects in 3.2 -7.8% of pregnancies complicated by AED monotherapy, and 6.0 -9.3% in AED polytherapy [Artama et al, Canger et al, 1999;Cunnington et al, 2005;Kaaja et al, 2003;Kaneko et al, 1999;Mawer et al, 2010;Morrow et al, 2006;Samren et al 1999;Wide et al, 2004;Wyszynski et al, 2004;. The meta analysis of 26 studies compiled by Tomson and Battino revealed a major congenital malformation (MCM) rate of 6.1% in offspring of women with epilepsy who were treated with AEDs, 2.8% among children of women with untreated epilepsy, and 2.2% in the healthy control group .…”
Section: Introductionmentioning
confidence: 99%